Ignorance is not bliss. The importance of media literacy in Singapore, in the age of globalised media. - Phang, Anna Seow May. (2008)
This study showed the importance of media education in promoting media literacy skills among students as indicated by significant differences in five of the eight media literacy skills that were studied. Overall, the media respondents faired significantly better than the non-media respondents by achieving a "high" skill level vs. a medium skill level for the non-media students.